Failure Analysis and Prevention of a Heavy-Duty Industrial Vibrating Feeder - YAYLA, PAŞA (My University, 2024)
Vibrating feeders play a vital role in numerous industries by facilitating the transfer of materials. Achieving the ideal material flow rate depends on the efficient operation of the feeder. Vibrating feeders are standard in material handling applications across multiple industries. This article deals with finite element model (FEM) analysis, and an investigation aimed at failure analysis and prevention of heavy-duty industrial vibrating feeders to: (i) investigate the causes of failure experienced during the dynamic phases of vibrating feeders, (ii) provide comprehensive information about the system, (iii) foresee the potential improvements to eliminate the cause of failure, and (iv) extend the lifetime of the system. The failed vibrating feeder was studied using ANSYS to investigate the stresses and deformations. Taking into account the analysis results, the location of the failure was identified, the design of the failure was improved, and the causes of the failure were eliminated by modifying the original design of the vibrating feeder. The study also clarifies the theory behind vibrating feeder technology and the importance of its design. Complete FEM analyses were conducted to calculate the stress and strain distributions together with vibration, fatigue, and frequency analyses in the original and modified vibrating feeders to reveal the differences between the two designs.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; MALZEME BİLİMİ, KOMPOZİTLER; MÜHENDİSLİK, İMALAT; Engineering, Computing & Technology (ENG); ENGINEERING; MATERIALS SCIENCE; ENGINEERING, MECHANICAL; MATERIALS SCIENCE, COMPOSITES; ENGINEERING, MANUFACTURING; Genel Malzeme Bilimi; Fizik Bilimleri; Emniyet, Risk, Güvenilirlik ve Kalite; Malzemelerin mekaniği; Makine Mühendisliği; General Materials Science; Physical Sciences; Safety, Risk, Reliability and Quality; Mechanics of Materials; Mechanical Engineering; Critical frequency; Fatigue crack; FEM; Mode analysis; Vibrating feeders